2002
DOI: 10.1021/ja025823y
|View full text |Cite
|
Sign up to set email alerts
|

Dicubyl Disulfide

Abstract: Dicubyl disulfide (1) has been prepared in six steps from commercially available dimethyl-1,4-cubanedicarboxylate in 47% overall yield. In the final step, the previously unknown cubanethiol 2 was oxidized to disulfide 1. X-ray crystallography for 1 reveals the shortest tetragonal C-S bond on record (1.771 A). In contrast to previous generalizations, density functional theory calculations predict a low S-S rotation barrier similar to that for t-BuSSBu-t. Low-temperature (13)C NMR (600 MHz) confirms the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…[18][19][20] While various individual observations regarding the tendency of monohalogenated cubanes to undergo metalhalogen exchange have been reported, [19][20][21] no systematic study has been performed. 20,[22][23][24] This led us to expand our initial synthetic program from reactants solely designed for Pd(II)-catalyzed reactions, to incorporate other systems and elements of synthetic interest, namely carbon-based electrophiles or 2nd row elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] While various individual observations regarding the tendency of monohalogenated cubanes to undergo metalhalogen exchange have been reported, [19][20][21] no systematic study has been performed. 20,[22][23][24] This led us to expand our initial synthetic program from reactants solely designed for Pd(II)-catalyzed reactions, to incorporate other systems and elements of synthetic interest, namely carbon-based electrophiles or 2nd row elements.…”
Section: Introductionmentioning
confidence: 99%
“…24 As a conclusion to the work on lithiated cubanes an alternative and more general method for the introduction of sulfur onto the cubane core in a milder fashion was investigated. Reaction of 4 with a sulfenyl chloride (derived from an odorless thiol which undergoes ready base deprotection to the free thiol [33][34][35] ) was found to give a low yield of the sulfur appended cubane 18 (Table 2, Entry 14).…”
mentioning
confidence: 99%
“…The thiol group is known to form a disulfide bond by a mild oxidizing agent such as iodine 24) . Our HPLC analysis indicated that the formation of disulfide bond was also observed simply by exposing to atmospheric oxygen in solutions.…”
mentioning
confidence: 99%
“…The ortho-metalation/carboxylation and functional group manipulation was repeated twice more to arrive at the pentasubstituted derivative (178), which was hydrolyzed to the corresponding tetraacid (179). The four carboxylic acid groups were reduced with LiAlH 4 and the resulting tetrahydroxymethyl groups were protected as acetates (180). Dimethyldioxirane oxidation of the amide gave the corresponding acid, which was then subjected to the Barton decarboxylation sequence: treatment with thionyl chloride, followed by 2-pyridinethiolate N-oxide sodium salt to form the thiohydroxamate ester, and then irradiation in the presence of t-butylthiol to give decarboxylated cubane 181.…”
Section: Nitrocubanesmentioning
confidence: 99%
“…179 It was thought that by oxidizing cubanethiol 206 to dicubyl disulfide 207 it would be stable enough for X-ray crystal structure as well as NMR studies. 180 Dicubyl disulfide was synthesized in a 47% yield from the starting 1,4-diester (13) and the X-ray structure analysis showed a C−S−S-C dihedral angle of 86.5°. This angle is 20−30°lower than other disulfides bearing tertiary carbons at sulfur.…”
Section: Cubane Sulfidesmentioning
confidence: 99%